Porphyromonas spp. have an extensive host range in ill and healthy individuals and an unexpected environmental distribution: a systematic review and meta-analysis - Acuña Amador, Luis Alberto (2020)
Studies on the anaerobic bacteria Porphyromonas, mainly focused on P. gingivalis, have revealed new bacterial structures, metabolic pathways, and physiologic functionalities. Porphyromonas are mainly described as being associated with mammals and involved in chronic oral infections and secondary pathologies such as cancers or neurodegenerative diseases. In this review, we collected and analyzed information regarding Porphyromonas isolation sites and associated conditions and showed that Porphyromonas are detected in numerous pristine and anthropic environments and that their host range appears wider than previously believed, including aquatic animals, arthropods, and birds, even if their predominant hosts remain humans, pets, and farm animals. Our analyses also revealed their presence in multiple organs and in a substantial proportion of healthy contexts. Overall, the growing numbers of microbiota studies have allowed unprecedented advances in the understanding of Porphyromonas ecology but raise questions regarding their phylogenic assignment. In conclusion, this systematic and meta-analysis provides an overview of current knowledge regarding Porphyromonas ecological distribution and encourages additional research to fill the knowledge gaps to better understand their environmental distribution and inter- and intra-species transmission.